Kontribusi Usahatani Kelapa Dalam Terhadap Pendapatan Petani di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Ningsih, Rozaina (Universitas Batangahari Jambi, 2025)
Tungkal Ilir sub-district in West Tanjung Jabung Regency has a hereditary coconut farm. Despite being one of the central coconut sub-districts in Jambi Province, the productivity of the harvest is still low at 1 ton/ha/year (copra) and 4000 grains or 1.5 tons/ha/year (whole coconut). This low productivity causes the source of income of farmer families not only comes from coconut farming, but some are obtained from farming other commodities and non-farm work. This study aims to 1) determine the description of coconut farming in Tungkal Ilir District, 2) Knowing the income of deep coconut farming in Tungkal Ilir District, and 3) Analyzing the contribution of deep coconut farming to farmers' income in Tungkal Ilir District, West Tanjung Jabung Regency. The results showed that 1) Coconut farming is a hereditary crop cultivated in the village of Tungkal I Village and Teluk Sialang Village in Tungkal Ilir District, the average use of labor uses labor within the family and labor outside the family if needed, 2) The average production cost of coconut farming is Rp1,187,447/ha/year which consists of fixed costs of Rp80.691/ha/year and variable costs of Rp1,031,445/ha/year. The average cost of revenue amounted to Rp15,138,211 /ha/year and the income of deep coconut farming amounted to Rp14.026.076/ha/year, 3) The average contribution of coconut farming income The average coconut farm income contribution of 27% falls into the medium category (20% - 50%) which indicates that farmers are not dependent on coconut farming alone and have other sources of income to meet their needs.